2019
DOI: 10.1177/2332858419872701
|View full text |Cite
|
Sign up to set email alerts
|

Using a Sequential Multiple Assignment Randomized Trial (SMART) to Develop an Adaptive K–2 Literacy Intervention With Personalized Print Texts and App-Based Digital Activities

Abstract: This study employs a sequential multiple assignment randomized trial (SMART) design to develop an adaptive intervention with personalized print and digital content for kindergarten to Grade 2 children (n = 273). In Stage 1, we ask whether it is better for children to receive an adaptive intervention based on (a) 10 conceptually coherent texts or (b) 10 leveled texts on a range of topics. In Stage 2, we ask how best to encourage nonresponding children. Findings indicate that children who received either concept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 57 publications
3
27
0
Order By: Relevance
“…Our family event participation rates are similar to or better than other family engagement studies where families complete 35% to 75% of offered events/activities (e.g., Bierman et al, 2015;Justice et al, 2018;Kim et al, 2019). For example, a recent family program held a kickoff event to provide informational science texts and other books with a summer reading app for kindergarten through Grade 2 (Kim et al, 2019). About 35% to 40% of parents attended this event, compared to 56% of parents who attended the first TT STEM event.…”
Section: Feasibility and Redesigning To Address Barriers To Informal ...supporting
confidence: 71%
See 2 more Smart Citations
“…Our family event participation rates are similar to or better than other family engagement studies where families complete 35% to 75% of offered events/activities (e.g., Bierman et al, 2015;Justice et al, 2018;Kim et al, 2019). For example, a recent family program held a kickoff event to provide informational science texts and other books with a summer reading app for kindergarten through Grade 2 (Kim et al, 2019). About 35% to 40% of parents attended this event, compared to 56% of parents who attended the first TT STEM event.…”
Section: Feasibility and Redesigning To Address Barriers To Informal ...supporting
confidence: 71%
“…We found that across treatments, 50% to 71% of parents attended at least one of the six workshops. Our family event participation rates are similar to or better than other family engagement studies where families complete 35% to 75% of offered events/activities (e.g., Bierman et al, 2015;Justice et al, 2018;Kim et al, 2019). For example, a recent family program held a kickoff event to provide informational science texts and other books with a summer reading app for kindergarten through Grade 2 (Kim et al, 2019).…”
Section: Feasibility and Redesigning To Address Barriers To Informal ...supporting
confidence: 68%
See 1 more Smart Citation
“…It is possible that these satisfaction data are overestimated because, out of respect for perceived museum experts, parents reported that the events were engaging and useful; this is common when families perceive a hierarchical relationship ( McWayne et al, 2022 ). Other family engagement studies show families complete 35–75% of offered activities ( Justice et al, 2018 ; Kim et al, 2019 ; Welsh et al, 2020 ). We found significantly higher workshop attendance for families with higher paternal education levels and trends for higher income and White families attending more events.…”
Section: Discussionmentioning
confidence: 99%
“… 2 Kim et al (2019) investigated an app using informational text, but the focus was on developing an adaptive intervention and increasing the response rate rather than learning. Some studies have included digital media, but only to support the primary intervention (e.g., Neuman et al, 2021, and Silverman & Hines, 2009, both targeting vocabulary). …”
mentioning
confidence: 99%